Synthesis of polyoxygenated dibenzo[a, e]cycloheptatrienes. Issue 15 (13th April 2017) - Chan, Chieh-Kai; Chan, Yi-Ling; Tsai, Yu-Lin; Chang, Meng-Yang
Abstract: A successive route for the synthesis of substituted dibenzo[ a, e ]cycloheptatriene1 was established by the reduction of 2-allylbenzaldehyde4, the BF3 ·OEt2 -mediated intermolecular coupling of 2-allylphenylmethanol5 with oxygenated benzenes6, the olefinic oxidative cleavage of7 and the intramolecular ring-closure of8 . Functionalized anthracene13 were prepared from 2-vinylbenzaldehyde9 . The key structures were confirmed by X-ray single crystal diffraction analysis. Graphical abstract: